Problems of Globalism in World Literature (Uzbekistan Open Conference, 2025)
The article examines the forms, styles, and manifestations of global issues in world literature. It summarizes the importance of interpreting a literary work not only through its individual elements, plot, composition, and expressive devices, but also through the place and time (chronotope) in which the events unfold.